Knowledge, Attitude, and Practice of Parents Regarding Children's Eye Care: A Cross-Sectional Study from Southwestern Saudi Arabia - Abdulaziz H. Alhazmi; Osama A. Mobarki; Rana A. Sumayli; Revan Abdulrahman Arishi; Fatimah N. Hakami; Naif A. Gharwi; Ehab F. Hakami; Ebrahim M. Abulqusim; Dhiyaa A. Otayf; Ismail Abuallut (The Journal of Medicine, Law & Public Health)
Abstract—Introduction: Eye care in children is of critical importance, as numerous pathologies can arise during childhood with the risk of serious consequences, including blindness. Parents' knowledge, attitudes, and practices in this regard are therefore crucial, as they significantly influence their children's eye health. This study aimed to assess the knowledge, attitudes, and practices (KAP) of parents regarding children's eye care in the Jazan region of southwestern Saudi Arabia.